Melatonin's protective effect on the salivary gland against ionized radiation damage in rats. (12th January 2016) - Cakmak Karaer, Isil; Simsek, Gokce; Yildiz, Azibe; Vardi, Nigar; Polat, Alaadin; Tanbek, Kevser; Gurocak, Simay; Parlakpinar, Hakan
Abstract : Objectives: The aim of this study was to examine the effects of melatonin on ionized radiation‐induced salivary gland damage using an experimental model. Materials and Methods: Thirty‐two rats were randomized into four groups: (i) the control group (C, n = 8) that received intraperitoneal (i.p.) 0.9% NaCl; (ii) the melatonin group (M, n = 8) that received i.p. 5 mg/kg melatonin; (iii) the radiotherapy group (RT, n = 8) that underwent irradiation; (iv) the melatonin plus radiotherapy group (M+RT, n = 8) that received i.p. 5 mg/kg of melatonin, followed by irradiation 30 min later; and (v) the radiotherapy plus melatonin group (RT+M, n = 8) that received irradiation followed by i.p. 5 mg/kg of melatonin 30 min later. The medications and irradiation were administered for 5 days and the salivary glands of the rats were excised 10 days later; the histopathological changes in the salivary glands were assessed and biochemical analyses were conducted (tissue levels of malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), reduced glutathione (GSH), total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI)). Results: Regardless of whether melatonin was administered before or after radiotherapy, melatonin decreased the radiation‐induced parotid and submandibular histological damage. In addition, regardless of whether administration occurred before or after radiotherapy, melatonin decreased oxidative stress markers, such as MDA, TOS, and OSI. On the contrary, levels of antioxidative markers, such as CAT and GPx, were increased by melatonin. Conclusions: Melatonin may have a significant protective effect on salivary gland damage secondary to ionizing radiation.